LIZARDIA CAPRICORNIA NEW STATUS (POLYCHAETA, HESIONIDAE), INCLUDING MORPHOLOGICAL DATA AND BIOGEOGRAPHIC NOTES - Costa, Dimítri de Araújo; da Silva, Francisco de Assis; Christoffersen, Martin Lindsey; Furtado, Gil Dutra; Nova Esperança, Revista de Ciências da Saúde (Revista de Ciências da Saúde Nova Esperança, 2017)
In 2000, the uninominal taxon capricornia Pleijel & Rouse was established as part of a phylogenetic proposal for the taxon Hesionidae (Annelida, Polychaeta), reported from the Great Barrier Reef, Australia. In that article, Pleijel & Rouse affirmed that the species should not be recognized as any special species taxa; thus, the species must be named as a Least-Inclusive Taxonomic Unit (LITU); taxon names refer to monophyletic groups only. The International Code of Phylogenetic Nomenclature (PhyloCode) does not totally reject Linnean nomenclature, but interprets taxa as belonging to species lineages or to supraspecific taxa without ranks. In 2005, Pleijel & Rouse erected the taxon Lizardia, including the monotypic species Lizardia hirschi from the same locality of capricornia (Great Barrier Reef). According to the PhyloCode, and on the basis of morphological data and biogeog raphic notes, we determine that capricornia should be called Lizardia capricornia new status, constituting the sister taxon of the species L. hirschi, both being nested within the monophyletic taxon Lizardia.